BİLGİSAYAR ÖĞRETMENLERİNİN BİR EĞİTİM ARACI OLARAK BİLGİSAYARA İLİŞKİN TUTUMLARI. - AKSOY, Mehmet Emin (Electronic Turkish Studies)
This research was carried out with a 97% participation rate to measure the attitudes of a total of 67 computer teachers consisting of 22 female and 45 male computer teachers working in the central and central schools of the city of Tokat with an educational tool.In the research, information collection tool consisting of 3 parts was used. The personal information constituting the first part was formed from 25 questions. The second part of the self-assessment format was formed from 34 attitude schedules. Section 3 is composed of 4 sub-sections.These sections included a total of 134 teacher attitude statements, including 34 selfassessed, 19 on the educational policy and philosophy, 15 on the tracked approach, 54 on the training program's items and 12 on teacher training, and in this frame they gave themselves the values of "good", "medium" and "not good".According to the findings in the research, teachers are now raised from one source, education faculties.One of the most important findings of the research is the lack of attitude differences among the attitudes of the male and female teachers in the determined categories.It is another important finding of research that all teachers should have in sights in to the center of teaching students. Despite the fact tha tmost of the teachers do not have experience abroad, they must be following the technology constantly, which is one of the positive attitudes of the research results. Teachers have not found any comment on theire conomic in come.